Optimal scheduling study of green warehousing microgrid based on improved sparrow search algorithm - Liu, Liyang; Zhang, Shiyu; Zhang, Hongdi; Zhang, Ziyan; Liu, Yudong (Frontiers in Energy Research, 2024)
Combining green warehousing with wind-solar-storage systems can improve the current situation of green warehousing with economic power consumption, energy saving, and emission reduction. To realize the efficient and stable operation of the wind-solar-storage microgrid, this paper proposes a microgrid optimal scheduling strategy based on the Improved Sparrow Algorithm (ISSA). Firstly, a comprehensive benefit model is established based on the economic and environmental benefits of microgrid daily operation. Then, an innovative improved sparrow search algorithm is proposed, which aims to improve the global search and local search capability of the microgrid scheduling problem by introducing improvements such as Logistic-Circle chaotic mapping, Bottle Sea Sheath swarm optimization algorithm, dynamic inertia weights, water wave dynamic factor, and Cauchy-Gaussian variational strategy. Finally, the microgrid optimal scheduling model is solved by the improved sparrow search algorithm and compared with other algorithms. In this paper, Matlab 2016b is used for simulation, and the simulation results show that the ISSA algorithm outperforms other algorithms in terms of solution stability and optimization search capability. Under three modes of operation, ISSA improves the microgrid operation revenue by 6.29%, 5.98%, and 6.31% at least. Therefore, the optimal scheduling scheme obtained based on ISSA improves the daily operating total revenue and the system operation stability of the microgrid.